2019
DOI: 10.1177/0163278719827997
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evaluation of the Persian eHealth Literacy Scale (eHEALS) Among Elder Iranians With Heart Failure

Abstract: The purpose of the present study was to examine the psychometric properties of the eHealth Literacy Scale (eHEALS) using classical test theory and modern test theory among elderly Iranian individuals with heart failure (HF). Individuals with objectively verified HF (n=388; 234 males; mean age=68.9±3.4) completed the (i) eHEALS, (ii) Hospital Anxiety and Depression Scale, Short-Form 12, (iii) 9-item European Heart Failure Self-care Behavior Scale, and (iv) 5-item Medication Adherence Report Scale. Two types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
77
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 30 publications
7
77
1
Order By: Relevance
“…25 The psychometric properties of the eHEALS are supported by its confirmed one-factor structure. 25…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…25 The psychometric properties of the eHEALS are supported by its confirmed one-factor structure. 25…”
Section: Introductionmentioning
confidence: 74%
“…The eHEALS has eight items rated on a five‐point Likert scale (1 = strongly disagree ; 5 = strongly agree ). A higher eHEALS score indicates a higher level of confidence in using, finding, and evaluating internet‐related information to make health‐related decisions, that is, greater perceived eHealth literacy . The psychometric properties of the eHEALS are supported by its confirmed one‐factor structure …”
Section: Methodsmentioning
confidence: 86%
“…The original English version 16 has been translated into several languages, such as Portuguese, 21 Dutch, 22 Hebrew, 23 German, 24 Japanese, 25 Spanish, 26 and Turkish. 27 In general, previous studies have shown solid values for internal consistency and reliability of the eHEALS. In their early work, Norman and Skinner 16 found a Cronbach's alpha coefficient of 0.88 on the total scale.…”
Section: Introductionmentioning
confidence: 89%
“…Later studies have reported Cronbach's alpha coefficients between 0.80 and 0.97. 19,22,23,[26][27][28] The structural components of the eHEALS have been widely discussed, 12 and many studies have found that it appears as a unidimensional scale. 12,22,28 This was also concluded in the initial work by Norman and Skinner.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the present study was to apply advance psychometric testing methods, including CFA (utilizing classical test theory) and the Rasch model (utilizing modern test theory; Lin et al 2019b), to examine the psychometric properties among Persian speakers. More specifically, participants from two countries (Iran and Afghanistan), whose official language is Persian, were recruited to understand whether the SBS is valid in both countries.…”
mentioning
confidence: 99%